PENERAPAN METODE BERCERITA BERBASIS ANIMASI UNTUK MENINGKATKAN KEMAMPUAN EKSPRESI DAN KEMAMPUAN BERBICARA - Wiwisti Herawati (DIADIK, 2023)
The purpose of this study was to describe the application of animation based storytelling methods to improve children's expression and speaking skills and to analyze their effectiveness compared to the learning that has been done by teachers (conventional methods in group B at TK Pertiwi II Bengkulu City. This type of research uses a combination of Classroom Action Research (CAR) with quasi-experimental. This is done for the purpose of broadening and deepening understanding of the conditions that occur in the field. Subject of this research are in group B at TK Pertiwi II Bengkulu City (B1 group for CAR, B2 and B3 for quasi-experimental). This research uses a Sequential Exploratory Design research design. Analyze used in this research are mean, pensentage and t test. The tools used in data collection are observation sheets. The results of classroom action research showed an increase in children's expression and speaking skills between cycles. The application of the animation-based storytelling method was effective in improving speaking skills. The implication of this research is that the teacher can make the application of the storytelling method more effective. through animation-based media as a daily learning method, especially in early childhood learning group B. The results of this study recommend that teachers can prefer learning models and methods as well as learning media that can improve aspects of child development